2020
DOI: 10.1002/mgg3.1236
|View full text |Cite
|
Sign up to set email alerts
|

Development of Chinese genetic reference panel for Fragile X Syndrome and its application to the screen of 10,000 Chinese pregnant women and women planning pregnancy

Abstract: Background Fragile X syndrome (FXS) is the most common inherited form of intellectual disability caused by a CGG repeat expansion in the 5′ untranslated region of the FMR1 gene. When the number of repeats exceeds 200, the gene becomes hypermethylated and is transcriptionally silenced, resulting in FXS. Other allelic forms of the gene that are studied because of their instability or phenotypic consequence include intermediate alleles (45–54 CGG repeats) and premutation alleles (55–200 repeats). Normal alleles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…Since our study had a much smaller sample size than did the Hung's and the Gao's studies, this may also introduce bias to the observed frequency of PM. In our cohort, the frequency of IM was 1/107, close to that (1/130) observed by Gao and colleagues in Chinese women of childbearing age (Gao et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Since our study had a much smaller sample size than did the Hung's and the Gao's studies, this may also introduce bias to the observed frequency of PM. In our cohort, the frequency of IM was 1/107, close to that (1/130) observed by Gao and colleagues in Chinese women of childbearing age (Gao et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, recent data from a large cohort of Chinese pregnant women (n = 20,188) showed that the prevalence of PM allele for FXS was as high as 1 in 777, indicating that reproductive FXS carrier screening in this population might be cost‐effective (Hung et al, 2019 ). The prevalence of PM carrier in our cohort was 1/1071, which is slightly lower than that (1/777) observed in the large cohort aforementioned and that (1/634) recently observed in a cohort consisting of 10,145 Chinese women of childbearing age (Gao et al, 2020 ). This difference may result from the inherent bias of our study design.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Therefore, a potential cost of 625,000 USD would be required due to the life-cycle burden of FXS patients. In this context, population-based screening would be more cost-saving than targeted screening for preventing the birth of FXS patients (Tables 7 and 8 According to these studies, which had relatively large sample sizes (over 5000), the prevalence of FXS carriers in the general population is 1/530-1/788 in South Korea and 1/564 in Northern China 18,20,21 , while the prevalence of FXS carriers in a population without a family history of FXS-associated conditions is 1/781-1/846 in South Korea and 1/776 in Taiwan [19][20][21] . Ma et al reported a higher prevalence (1/410) of FXS carriers in reproductive women in Northern China 24 .…”
Section: Cost-effectiveness Analysismentioning
confidence: 99%